Hemicraniectomy in elderly patients with space occupying media infarction: improved survival but poor functional outcome. Issue 2 (1st February 2001) - Holtkamp, M; Buchheim, K; Unterberg, A; Hoffmann, O; Schielke, E; Weber, J R; Masuhr, F
Abstract : OBJECTIVE: To assess the survival rate and functional outcome in elderly patients with space occupying supratentorial infarction who underwent hemicraniectomy compared with those who received medical treatment alone. METHODS: All patients older than 55 years with space occupying middle cerebral artery (MCA) infarction treated in our clinic between January 1998 and July 1999 were included in this retrospective analysis. Patients were eligible for decompressive surgery if they were younger than 75 and had no severe comorbidity. Hemicraniectomy was performed regardless of the affected hemisphere. All patients were followed up for assessment of functional outcome; data were assessed according to the Barthel index and modified Rankin scale and cover a period of 3 to 9 months after infarction. RESULTS: Twelve out of 24 patients underwent hemicraniectomy. Eight patients who were operated on survived; only one patient died of transtentorial herniation, three other deaths were due to medical complications. None of the survivors had a Barthel score above 60 or a Rankin score below 4. Nine out of 12 medically treated patients died of transtentorial herniation, one patient died of medical complications. The two surviving patients had a Barthel score below 60 and a Rankin score of 4. CONCLUSIONS: Craniectomy in elderly patients with space occupying MCA infarction improves survival rates compared with medical treatment alone. However, functional outcome and level of independence are poor. Craniectomy in elderly patients should not be performed unless a prospective randomised trial proves beneficial.